Improving Teachers' Teaching Abilities Through Supervision Activities Using Group Techniques and Visits Class at SMAN 1 Sigi - Januddin, Herman (Universitas Negeri Makassar, 2023)
Supervision is a coaching activity that is planned to help teachers and other school employees carry out their work effectively. Therefore, the aim of this research is to improve teachers' teaching abilities through supervision activities using group techniques and class visits at SMN 1 Sigi. The research method used was school action research (PTS) with research subjects consisting of 6 subject teachers. The data collection techniques used are observation and documentation with data analysis techniques using qualitative and quantitative analysis. The results of the research showed that the implementation of principal supervision using group techniques and approaches supported by supervision of class visits was declared successful and completed in the second cycle because all indicators of success had been met in the implementation of the second cycle activities